2021
DOI: 10.1093/cid/ciab884
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Sustained Cellular and Humoral Immunities in Coronavirus Disease 2019 (COVID-19) Convalescents

Abstract: Background The longitudinal antigen-specific immunity in COVID-19 convalescents is crucial for long-term protection upon individual re-exposure to SARS-CoV-2, and even more pivotal for ultimately achieving population-level immunity. To better understand the features of immune memory in individuals with different disease severities at one year post-disease onset we conducted this cohort study. Methods We conducted a systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
70
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 28 publications
9
70
2
Order By: Relevance
“…Recent data from animal models, therapeutic use of neutralizing monoclonal antibodies, and convalescent plasma in a clinical setting suggest a critical role for nAbs in controlling SARS-CoV-2 infection and re-infection [15][16][17][18][19][20][21][22] , while a key question that has not yet been addressed is whether COVID-19 convalescents could maintain long-lasting antibody-mediated protective immunity. Studies have investigated the dynamic change and longevity of the binding and nAb response in COVID-19 convalescents, and indicated that the nAb response in COVID-19 convalescents could be maintained for up to one year after the onset of symptoms, accompanied by a decrease in nAb titres 14,[23][24][25][26] .…”
mentioning
confidence: 99%
“…Recent data from animal models, therapeutic use of neutralizing monoclonal antibodies, and convalescent plasma in a clinical setting suggest a critical role for nAbs in controlling SARS-CoV-2 infection and re-infection [15][16][17][18][19][20][21][22] , while a key question that has not yet been addressed is whether COVID-19 convalescents could maintain long-lasting antibody-mediated protective immunity. Studies have investigated the dynamic change and longevity of the binding and nAb response in COVID-19 convalescents, and indicated that the nAb response in COVID-19 convalescents could be maintained for up to one year after the onset of symptoms, accompanied by a decrease in nAb titres 14,[23][24][25][26] .…”
mentioning
confidence: 99%
“…This suggests an increased immune response with higher viral loads and inflammatory mediators during acute infection. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Peptides with a purity of over 95% were synthesized by Beijing Scilight Biotechnology Corporation, and the peptide powders were dissolved in DMSO before use. An HLA-A*1101 tetramer complexed with SARS-CoV-2-specific peptide was generated in our laboratory as described previously for the preparation of other HLA class I tetramers (6).…”
Section: Methodsmentioning
confidence: 99%
“…CD8 + T cells recognize antigenic peptides presented by major histocompatibility complex I (MHC-I) through T cell receptors (TCRs) and are activated to kill virusinfected target cells (4)(5). Nucleocapsid (N) protein is one of the main structural proteins of SARS-CoV-2 and can trigger broad T-cell responses in humans (6). Herein, an overlapping peptide pool covering the full length of N protein was designed, overlapping peptides with positive T-cell activating potency in COVID-19 convalescents were screened, and CD8 + T cell epitopes in the positive overlapping peptides were further identified.…”
Section: Introductionmentioning
confidence: 99%